Mass Occurence of Stink Bug Cyclopelta siccifolia (Westwood) (Heteroptera: Pentatomoidea: Dinidoridae) on Millettia pinnata (L.) Panigrahi, at Kannur, Kerala, Southern India - Nair, Vinayan (Journal of the Bombay Natural History Society (JBNHS), 2014)
No abstract.